2008
DOI: 10.1007/s10310-007-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter decomposition of dominant tree species of Namdapha National Park, Arunachal Pradesh, northeast India

Abstract: Rates of weight loss and nutrient (N and P) release patterns were studied in the leaf litter of the dominant tree species (Ailanthus grandis, Altingia excelsa, Castanopsis indica, Duabanga sonneriatioides, Dysoxylum binectariferum, Mesua ferrea, Shorea assamica, Taluma hodgsonii, Terminalia myriocarpa and Vatica lancefolia) of a tropical wet evergreen forest of northeast India. Nitrogen and phosphorus mineralization rate and decay pattern varied significantly from species to species. In general, the decay patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
9
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
5
9
0
4
Order By: Relevance
“…Likewise, Jamaludheen and Kumar 27 reported a positive yet non-significant relation of soil moisture with residual litter weight. Soil total N also showed a positive correlation with decay rate, which corroborates with reports by other workers 6,32 . According to Liu et al 32 , N availability is essential for litter decomposition, as increased soil N can cause changes in the soil nutrient level and decomposers as well as the quality of decomposing litter.…”
supporting
confidence: 82%
See 4 more Smart Citations
“…Likewise, Jamaludheen and Kumar 27 reported a positive yet non-significant relation of soil moisture with residual litter weight. Soil total N also showed a positive correlation with decay rate, which corroborates with reports by other workers 6,32 . According to Liu et al 32 , N availability is essential for litter decomposition, as increased soil N can cause changes in the soil nutrient level and decomposers as well as the quality of decomposing litter.…”
supporting
confidence: 82%
“…The rate of decomposition of foliar litter was high in the study site, which was revealed from the fairly high value of annual decomposition constant (k). The recorded value (k year -1 ) in the present study is comparable with those of Barbhuiya et al 6 (1.04-5.37), Upadhyaya et al 21 (1.3-8.19). However, it is relatively higher than ranges reported by several others workers 11,20,24,25 .…”
supporting
confidence: 81%
See 3 more Smart Citations